Bilateral Subclavian Artery Stenosis: Anaesthetic consideration - Nanda Gopal Mandal; Indrajeet Mandal; Kate Barber (Global Journal of Anesthesiology - Peertechz Publications, 2017)
Subclavian artery stenosis (SAS) is a relatively rare condition, even more so for its bilateral existence. In a study [1], the prevalence of SAS was 1.9% in the free-living cohorts and 7.1% in the clinical cohorts. SAS was significantly associated with smoking and higher levels of systolic blood pressure. Higher levels of high-density lipoprotein cholesterol were inversely and signifi cantly associated with SAS. In regression analyses relating SAS to other cardiovascular diseases, the only significant finding was with peripheral arterial disease. The presence of this condition leads to erroneously low blood pressure recoded in the ipsilateral brachial artery or radial artery. The conventional anaesthetic challenge for these patients could be maintaining organ perfusion (especially the cerebral perfusion) and thus avoiding ischaemic damage when the actual blood pressure is unknown. We report an interesting patient with bilateral subclavian stenosis who underwent prolonged surgery for a repair of massive parastomal hernia. This case was detected incidentally based on clinical findings. It was confirmed subsequently by CT angiogram. The surgery was performed under general anaesthesia and the patient was discharged home unharmed.